Device physics underlying silicon heterojunction and passivating‐contact solar cells: A topical review. (15th January 2018) - Chavali, Raghu V. K.; De Wolf, Stefaan; Alam, Muhammad A.
Abstract: The device physics of commercially dominant diffused‐junction silicon solar cells is well understood, allowing sophisticated optimization of this class of devices. Recently, so‐called passivating‐contact solar cell technologies have become prominent, with Kaneka setting the world's silicon solar cell efficiency record of 26.63% using silicon heterojunction contacts in an interdigitated configuration. Although passivating‐contact solar cells are remarkably efficient, their underlying device physics is not yet completely understood, not in the least because they are constructed from diverse materials that may introduce electronic barriers in the current flow. To bridge this gap in understanding, we explore the device physics of passivating contact silicon heterojunction (SHJ) solar cells. Here, we identify the key properties of heterojunctions that affect cell efficiency, analyze the dependence of key heterojunction properties on carrier transport under light and dark conditions, provide a self‐consistent multiprobe approach to extract heterojunction parameters using several characterization techniques (including dark J‐V, light J‐V, C‐V, admittance spectroscopy, and Suns‐V oc ), propose design guidelines to address bottlenecks in energy production in SHJ cells, and develop a process‐to‐module modeling framework to establish the module's performance limits. We expect that our proposed guidelines resulting from this multiscale and self‐consistent framework will improve the performance of future SHJ cells as well as other passivating contact‐based solar cells. Abstract : An end‐to‐end modeling and characterization framework is essential for system development of heterojunction solar cell technology. In this paper, the authors discuss a multiscale and process‐to‐module modeling framework; review the technology milestones, current status, and levelized cost of energy–based cost analysis; and explain how the complexity of carrier transport and electrostatics define the performance and reliability characteristics of this promising solar cell technology.